Persepsi Remaja Terhadap Upaya Bunuh Diri dalam Film “Kembang Api” - Farhan Aditya Danendra; Augustin Mustika Chairil (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This mass Media can be the main media in mass communication activities that aim to spread messages to audiences. Film is a persuasive type of mass media. movies can greatly affect people's perception of the storyline and the message contained in the film. One of the problems in society is suicide. Suicide is a serious issue that can have a negative impact on a person's mental health. Films have a significant role in shaping adolescents ' perceptions of various issues, including suicide attempts. However, there is still a lack of understanding about teenagers ' perception of suicide scenes in films. Therefore, this study will fill this knowledge gap by analyzing adolescents ' perceptions of suicide scenes in the movie